2008
DOI: 10.1074/jbc.m801800200
|View full text |Cite
|
Sign up to set email alerts
|

The Diaphanous-related Formin FHOD1 Associates with ROCK1 and Promotes Src-dependent Plasma Membrane Blebbing

Abstract: Diaphanous-related formins (DRFs) mediate GTPase-triggered actin rearrangements to regulate central cellular processes, such as cell motility and cytokinesis. The DRF FHOD1 interacts with the Rho-GTPase Rac1 and mediates formation of actin stress fibers in its deregulated form; the physiologically relevant activities and molecular mechanisms of endogenous FHOD1, however, are still unknown. Here we report that FHOD1 physically associates via the N-terminal part of its FH2 domain with the central domain of ROCK1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 50 publications
(59 reference statements)
5
66
0
Order By: Relevance
“…Consistent with the requirement for ROCK, PM blebbing of adhering HeLa cells strictly required the activity of the GTPase and ROCK regulator RhoA, while activity of Rac1 and Cdc42 GTPases was dispensable (Supplementary information, Figure S1A and S1B). Finally and in line with previous results on blebs observed upon SH4-domain expression or filamin A deficiency, PM blebs were enriched in p-MLC, p-ERM and p-Src that displayed distinct localizations at blebs (Supplementary information, Figure S1C) [12,20]. Together, these results establish PM blebbing of adhering HeLa cells as a model system that mirrors the general characteristics of PM blebbing and in which blebbing is governed by Rho-ROCK signaling and F-actin remodeling.…”
Section: Adhering Hela Cells Display Dynamic Pm Blebbingsupporting
confidence: 75%
See 3 more Smart Citations
“…Consistent with the requirement for ROCK, PM blebbing of adhering HeLa cells strictly required the activity of the GTPase and ROCK regulator RhoA, while activity of Rac1 and Cdc42 GTPases was dispensable (Supplementary information, Figure S1A and S1B). Finally and in line with previous results on blebs observed upon SH4-domain expression or filamin A deficiency, PM blebs were enriched in p-MLC, p-ERM and p-Src that displayed distinct localizations at blebs (Supplementary information, Figure S1C) [12,20]. Together, these results establish PM blebbing of adhering HeLa cells as a model system that mirrors the general characteristics of PM blebbing and in which blebbing is governed by Rho-ROCK signaling and F-actin remodeling.…”
Section: Adhering Hela Cells Display Dynamic Pm Blebbingsupporting
confidence: 75%
“…Only few studies previously addressed the involvement of specific actin nucleators in PM blebbing. Using experimental systems in which PM blebbing was induced by genetic manipulation or protein overexpression, nucleators such as mDia1, mDia2, FHOD1, Arp2/3 that are also involved in the regulation of diverse additional cellular actin remodeling events were implicated in blebbing [12,[41][42][43]. In this present study, we conducted a comprehensive analysis of the involvement of endogenously expressed human actin nucleators in PM blebbing of adhering HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Run-on transcription assays revealed that the amount of nascent RNA is drastically diminished in the cells expressing the C-terminal portion, which in turn, is translocated to the nucleus (Ménard et al, 2006). Hannemann et al (2008) described that FHOD1, associated to ROCK1 is required for the membrane blebbing, which is dependent on F-actin integrity. Also, mammalian and Drosophila formins perform different roles during development and differentiated cells (Homem and Pfeifer, 2009;Massarwa et al, 2009;Matusek et al, 2006Matusek et al, , 2008.…”
Section: Fhos's Persistent Salivary Glands Exhibit Changes In the Actmentioning
confidence: 99%